Spontaneous Cutaneous Endometriosis of the Umbilicus - Thomas J. Gin; Alexander D. Gin; Douglas Gin; Alan Pham; Jennifer Cahill (Karger Publishers, 2013)
Cutaneous endometriosis that arises de novo, without a prior history of surgery, is a rare phenomenon. The clinical diagnosis of cutaneous endometriosis remains challenging due to the variable clinical appearance and symptoms of the condition, and therefore must be considered in the differential diagnosis of any umbilical lesion. We report a 31-year-old woman who presented with spontaneous cutaneous endometriosis of the umbilicus.